SIGMOBILE FY'05 annual report July 2004--June 2005. - Johnson, David B. (Mobile computing and communications review.)
Every year, as ACM's fiscal year ends annually on June 30, each SIG Chair is required to submit a report to ACM's SIG Governing Board that summarizes the highlights of the SIG's activities over the previous year. This article reproduces SIGMOBILE's Annual Report for the year July 1, 2004, through June 30, 2005. It has been an exciting, productive, and successful year for SIGMOBILE, and we hope you share in our excitement as we move forward to many more successes in the future.